Tailoring Colors by O Annulation of Polycyclic Aromatic Hydrocarbons. Issue 10 (23rd January 2017) - Miletić, Tanja; Fermi, Andrea; Orfanos, Ioannis; Avramopoulos, Aggelos; De Leo, Federica; Demitri, Nicola; Bergamini, Giacomo; Ceroni, Paola; Papadopoulos, Manthos G.; Couris, Stelios; Bonifazi, Davide
Abstract: The synthesis of O‐doped polyaromatic hydro‐ carbons in which two polycyclic aromatic hydrocarbon sub units are bridged through one or two O atoms has been achieved. This includes high‐yield ring‐closure key steps that, depending on the reaction conditions, result in the formation of furanyl or pyranopyranyl linkages through intramolecular C−O bond formation. Comprehensive photophysical measurements in solution showed that these compounds have exceptionally high emission yields and tunable absorption properties throughout the UV/Vis spectral region. Electrochemical investigations showed that in all cases O annulation increases the electron‐donor capabilities by raising the HOMO energy level, whereas the LUMO energy level is less affected. Moreover, third‐order nonlinear optical (NLO) measurements on solutions or thin films containing the dyes showed very good values of the second hyperpolarizability. Importantly, poly(methyl methacrylate) films containing the pyranopyranyl derivatives exhibited weak linear absorption and NLO absorption compared to the nonlinearity and NLO refraction, respectively, and thus revealed them to be exceptional organic materials for photonic devices. Abstract : Staring at the rainbow : π‐extended O‐doped polycyclic aromatic hydrocarbons were synthesized by high‐yielding ring‐closure reactions leading to the formation of furanyl or pyranopyranyl frameworks. Photophysical and electro chemical characterization showed that these compounds exhibit finely tunable optoelectronic properties (see figure), while third‐order nonlinear optical measurements revealed very good second hyperpolarizability values, which make them exceptional candidates for photonic applications.